Non-isolated integrated motor drive and battery charger based on the split-phase PM motor for plug-in vehicles - Serrano Guillén, Isabel; Bermejo Fernández, Álvaro (My University, 2013)
In electric vehicles and plug-in hybrid electric vehicles, the utility grid charges the vehicle battery through a battery charger. Different solutions have been proposed to reduce the size and cost of the charger. One solution to achieve this is to include the devices used in the traction circuit in the charger circuit; this is called an integrated motor drive and battery charger. A split-phase PM motor, a motor with double set of windings, gives the opportunity to implement different winding configurations to keep the motor at stand-still when it is connected to the grid. The motor will act as inductors in the charging process. This is an advantageous chance in order to use the motor in an integrated battery charger. In the current thesis, a non-isolated battery charger based on some of these special configurations is tested. Two different PM motors are utilized in proposed chargers. Different windings configurations have been practically tested. The main challenge is to keep the motor in stand-still during charge operation. Practical results show that with proposed schemes, the motors are in stand-still. A National Instrument CompactRIO system is used to perform the control of the integrated charger in the practical implementation. A brief explanation of the practical setup and a user guide for running the experimental system is included as well.
Keywords: Elkraftteknik; Electric power engineering